2016
DOI: 10.1111/inm.12214
|View full text |Cite
|
Sign up to set email alerts
|

Motivation for physical activity and exercise in severe mental illness: A systematic review of intervention studies

Abstract: There has been increasing interest for research on motivation for physical activity (PA) and exercise among individuals with severe mental illness (SMI). The aim of this systematic review is to summarize findings from all intervention studies on PA or exercise that either include empirical data on motivational constructs or apply motivational techniques/theories in their intervention. Systematic searches of seven databases were conducted from database inception to February 2015. Studies were eligible if they: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
40
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(48 citation statements)
references
References 68 publications
4
40
1
3
Order By: Relevance
“…The results of this study are similar to the results of the studies in the literature . Having the will and motivation are important to increase physical activities . The studies in the literature report that individuals with mental illness lack the motivation to attend and sustain physical activities .…”
Section: Discussionsupporting
confidence: 87%
“…The results of this study are similar to the results of the studies in the literature . Having the will and motivation are important to increase physical activities . The studies in the literature report that individuals with mental illness lack the motivation to attend and sustain physical activities .…”
Section: Discussionsupporting
confidence: 87%
“…Identifying and understanding the causes of physical activity behaviour is essential for developing lifestyle modification programmes designed to promote exercise . Barriers to participation in regular physical activity have been studied in various populations . Common obstacles include lack of time, health problems, bad weather, environmental considerations such as convenient access, safety and cost, lack of social support, professional guidance, and lack of self‐efficacy .…”
Section: Introductionmentioning
confidence: 99%
“…33, -1685Med. 33, (2016 been studied in various populations [9][10][11][12][13]. Common obstacles include lack of time, health problems, bad weather, environmental considerations such as convenient access, safety and cost, lack of social support, professional guidance, and lack of self-efficacy [11,14].…”
mentioning
confidence: 99%
“…Given that the "critical period" for patients with schizophrenia comes in the first 5 years, (Birchwood, Todd, & Jackson, 1998;Lutgens et al, 2015), treatment during this period alleviates the impact of the disorder. Along these lines, other studies incorporating motivational interview techniques have also attained excellent results (Barrowclough, 2011;Barrowclough et al, 2010;Beebe et al, 2012;Farholm & Sørensen, 2016;Fiszdon et al, 2016;Haddock et al, 2004;Vanderwaal, 2015;Wai et al, 2015).…”
Section: Discussionmentioning
confidence: 92%
“…Motivational interview (MI) were initially designed for substance abuse treatment (Miller & Rollnick, 1991),but they have also been applied to the treatment of schizophrenia. Some research has shown this method to be effective, although most of the existing evidence does concern substance abuse ( Baker et al, 2002;Graeber, Moyers, Griffith, Guajardo, & Tonigan, 2003;La Pietra, 2006;Martino, Carroll, Nich, & Rounsaville, 2006;Martino et al, 2000;Steinberg, Ziedonis, Krejci, & Brandon, 2004;Swanson, Pantalon, & Cohen, 1999), adherence to pharmacological treatment regimens (Depp, Lebowitz, Lacro, & Jeste, 2007;Drake et al, 2015;Fiszdon, Kurtz, Choi, Bell, & Martino, 2016;Kemp, Hayward, Applewhaite, Everitt, & David, 1996;Kemp, Kirov, Everitt, Hayward, & David, 1998;McCracken & Corrigan, 2008;O'Donnell et al, 2003;Rusch & Corrigan, 2002) and encouragement of physical exercise (Beebe et al, 2011(Beebe et al, , 2012Farholm & Sørensen, 2016). Other studies along similar lines have looked at aspects such as goal assessment (Corrigan, McCracken, & Holmes, 2001)and the development of insight (Rusch & Corrigan, 2002).…”
Section: Introductionmentioning
confidence: 99%